Pengaruh E-Service Quality, Brand Image dan Etika Bisnis Islam Terhadap Kepuasan Konsumen Shopee pada Mahasiswa Ekonomi Syariah dan Akuntansi di Universitas Jember Kampus Bondowoso - Jakfar, Muhammad; Purnamie Titisari; Agus Luthfi (UPT Penerbitan Universitas Jember, 2024)
Shopee is an online shopping platform that is widely used by people from various groups, from the lower middle class to the upper middle class. Shopee has powerful digital services and is accompanied by very easy payment methods and provides many promotions such as discounts and free shipping with or without a minimum purchase, this service is what makes Shopee one of the best e-commerce. The aim of this research is to determine and analyze the influence of E-Service Quality, Brand Image and Islamic Business Ethics on Consumer Satisfaction on the Shopee application. In this research, the Purposive Sampling method was used to obtain samples. Meanwhile, for this research method, a quantitative descriptive method approach is used. The research results can be concluded that partially there is a significant influence of E-Service Quality, Brand Image and Islamic Business Ethics on consumer satisfaction. Apart from that, the results of this research also show that there is a significant positive influence of the variabels E-Service Quality, Brand Image and Islamic Business Ethics simultaneously on Consumer Satisfaction. This indicates that these elements need serious attention for marketing because these variabels will influence consumer considerations in making purchasing decisions.